Trauma Masa Anak, Hubungan Romantis, dan Kepribadian Ambang - Wibhowo, Christin; DS So, Klara Andromeda (Faculty of Psychology, Universitas Gadjah Mada, 2019)
People with borderline personality features (BPF) are characterized by impulsive, emotionally unstable, have unsafe sexual activity, and other actions that are at risk to commit suicide. Although some of the behavior is not included in crime, but if there is no prevention, the BPF will endanger itself and its environment This study aims to determine the relationship of childhood trauma, a romantic relationship, with BPF. The hypothesis are, 1) there is relationship between childhood trauma and BPF;2) there is relationship between romantic relationships andBPF. This study using 77 participant wives aged 20-40 years. Collecting data using of Borderline Personality Scale, Childhood Trauma Scale and Romantic relation Scale. Data analysis with product moment.The result of this study are 1)there is a relationship between childhood trauma and borderline personality (r = 0.6, p <0.01); 2) there is relationship between romantic relationship and borderline personality (r = - 0.5= p<0.01).